Characterizing Middle School Students' Physical Literacy Development: A Self-Determination Theory-Based Pilot Intervention in Physical Education - Liu, Yang; Chen, Senlin (Frontiers in Sports and Active Living, 2022)
Purpose: Positive youth development (PYD) can be achieved through effective and purposeful instructions in physical education (PE) and other relevant experiences both in and beyond schools. Students' PYD is associated with their physical literacy (PL) development, which has become a primary emphasis of PE, especially in the United States, in recent years. This study aimed to (a) characterize middle school students' physical literacy (PL) and (b) capture their PL developing trajectories in light of receiving a self-determination theory (SDT)-based pedagogical workshop, with the long-term vision on PYD. Methods: Participants (N = 226) completed the Canadian Assessment of Physical Literacy (CAPL-2) in physical education (PE). A subsample (n = 49) received four workshop sessions over 8 weeks; and completed the CAPL-2 and participated in focus group interviews before and after the workshop. Results: Both boys and girls' CAPL-2 scores were in the “progressing” stage. Significant differences in PL and PL domains were observed by gender, grade, socioeconomic status (SES), body mass index (BMI), and race/ethnicity. The low PL group showed improvements in PL and PL domains. Interview data delineated positive PL developing trajectories for physical activity (PA) type, frequency, and intensity; perceived motives; and participation barriers. Conclusion: PL is a dynamic state that can be improved through purposeful PE. Future work should examine the effect (and implementation) of opportunities in (e.g., PE) and beyond schools (e.g., youth sports programs) to ultimately advance PYD.